Outdoor activities promoting mental and physical health and well-being in Sámi Early Childhood Education and Care institutions - Bjerklund, Monica; Åmot, Ingvild (Journal of Childhood, Education and Society, 2023)
This article explores the current situation of outdoor play for children in Sámi Early Childhood Education and Care institutions (ECECs) in Norway. The main objective is to discover how Sámi ECEC practices contribute to outdoor play and learning in early childhood education and community contexts by addressing the following research questions: How do Sámi ECEC staff emphasize outdoor activities and play in their daily practice, and how can these activities be regarded as a way of promoting mental and physical health and well-being? The sample comprises practitioners from seven Sámi ECEC institutions (ECECs) participating in focus-group and individual interviews. The main focus of the interviews was on Sámi ECECs as health-promoting arenas, and outdoor activities appeared to be important in this context. Stepwise-Deductive Induction was used as a qualitative research strategy in the analysis. The staff underline the importance of letting children attempt to be autonomous when it comes to physical and practical activities. They point to the importance of knowing the children and encouraging autonomous achievements. Traditionally, Sámi upbringing places emphasis on doing handicraft and daily work together with the children. The staff describe doing such daily outdoor activities as harvesting, handicraft, and food preparation together with the children as a way of maintaining Sámi culture. The main conclusion is that outdoor activities are important for promoting, experiencing, and contributing to Sámi pedagogy and children’s well-being in the Sámi ECECs.